Exploring the Integration between Corporate Social Responsibility and Human Resource Management Practices: Cases of SMEs in Johor, Malaysia - Salasiah Ma’erat; Omar, Siti Sarah; Mohd Asmadi Mohd Angsor (Research in Management of Technology and Business, 2024)
In this day, CSR has been a primary factor in how businesses recruit, retain, and motivate potential employees. Due to growing concern about CSR and the value of CSR to HRM in an organization, researchers have emphasized an increased interest in debating the integration between these categories. However, the lack of empirical research on the integration between CSR and HRM in practice has led to a lack of understanding of how these two ideas are linked in dynamic and complex organizational CSR. In order to bridge this knowledge gap, this exploratory study examines to what extent CSR is embedded in HRM functions, and proposes a framework for integration between CSR and HRM. The population of this research were SMEs in Malaysia, which have implemented CSR in their organization’s HRM function. This is positioned in an exploratory paradigm and uses qualitative research methods, based on data from an interview with SME companies in Malaysia. For the research instrument, researchers were used an interview method with selected SME employees. The interview information were analyzed by using thematic analysis and NVivo software. Findings revealed that SMEs companies value and implemented CSR that focusing on their external and internal stakeholder such as employees, customers, environment and society. In addition this study found that, CSR and HRM are linking function with two groups which CSR to HRM and HRM to CSR. This study provides both theoretical and practical contributions, especially in identifying the linking between CSR and HRM as well as role of HRM for the success of CSR operations. The framework enables the evaluation of the organization’s integrated socially responsible and human resource activities. Besides that, it help to discover and use the benefits resulting from the linkages between CSR and HRM; to utilize it for establishing CSR concepts and instructional objectives in industry and other private sector groups.